THE IMPACT OF PELVIC VIENS’ VARICOSE ON THE DEVELOPMENT OF HORMONAL DYSFUNCTION OF REPRODUCTIVE AGE’s WOMEN - Hryhorenko, А.М. (World of Medicine and Biology, 2012)
Varicose of pelvic veins is a pathology which occurs mainly in women of reproductive age. But nowadays we cannot find enough data about impact of pelvic venous stasis in idiopathic forms of infertility, pregnancy, childbirth and gynecological pathology. The purpose of our study was a retrospective study of case histories of patients who were treated in the hospital and research pathogenetic link between varicosis and the dysfunctions of reproductive system.
Keywords: pelvic varicose; gynecological pathology